1997
DOI: 10.1111/j.1095-8649.1997.tb01628.x
|View full text |Cite
|
Sign up to set email alerts
|

Histology of dart tag insertion sites in the epaulette shark

Abstract: Samples of dermal and epidermal tissues of epaulette sharks Hemiscyllium ocellatum were examined histologically to assess damage caused by tagging. Tissues from around tag sites were removed at time intervals ranging from 100 min to 284 days post-tagging. These samples showed acute and chronic responses to tagging. Acute responses consisted of localized tissue breakdown and haemorrhaging, and occurred within the first few hours after tag insertion. At 10 h post-tagging, an intermediate response was apparent. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A variety of encrusting organisms, such as filamentous algae, barnacles, sponges, and ascidians, have been found growing on recaptured tags (Davies and Joubert, 1966;Heupel and Bennett, 1997;Heupel et al, 1998). None of these studies, however, investigated the composition and magnitude of tag biofouling.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A variety of encrusting organisms, such as filamentous algae, barnacles, sponges, and ascidians, have been found growing on recaptured tags (Davies and Joubert, 1966;Heupel and Bennett, 1997;Heupel et al, 1998). None of these studies, however, investigated the composition and magnitude of tag biofouling.…”
Section: Discussionmentioning
confidence: 96%
“…The tag wound associated with dart tags consisted of an open wound, which appeared to be irritated by the continual movement of the tag streamer at the point of tag insertion. Heupel and Bennett (1997) concluded that although plastic headed dart tags often caused localized tissue disruption, the wounds were free of infection even in sharks whose tags were heavily fouled with algae. A larger percentage of sharks tagged with dart tags by members of the ORI tagging programme exhibited tag wounds than those tagged by members of the PEM tagging programme.…”
Section: Discussionmentioning
confidence: 97%
“…Conventional tagging is increasingly used to estimate and assess shark populations and movement and since 1962 the National Oceanographic and Atmospheric Administration's National Marine Fisheries Service Laboratory (NOAA-NMFS) 0165 has implemented a cooperative shark tagging program with recreational anglers and commercial fishers leading to the tagging of over 87,000 sharks (Kohler et al, 1998). However tag shedding appears common in a range of shark species, undermining viable population estimates (Davies and Joubert, 1967;Gruber, 1982;Carrier, 1985;Heupel and Bennett, 1997). By comparison, photo identification is a non-invasive method of identifying individuals that relies on cataloguing distinctive scars or markings originally developed to identify terrestrial animals and marine mammals that can be clearly seen (Katona et al, 1979;Arnbom, 1987).…”
Section: Introductionmentioning
confidence: 97%
“…In terms of individual identification, a great variety of methods have been used in fish population studies (Heupel & Bennett 1997). Artificial external marks such as tags are commonly used in shark studies (Ingram 1994, Kohler & Turner 2001.…”
Section: Introductionmentioning
confidence: 99%